Contrastive Linguo-Cultural Analysis of the Concept “Faith/Belief” - Harutiunian, Narine (Armenian Folia Anglistika, 2006)
The cultural concept, which is a multi-graded semantic formation (with its conceptual, imaginative and evaluative components) is a linguocultural unit. Faith that is an indispensable element of human life and acts as the basis of all moral values is a broader and more global metaphysical concept. Faith is the value which allows a human to perceive the hierarchy of other values. The article offers a contrastive analysis of three languages (English, Armenian and Russian) in the cultural tradition.